Zeitungsregionen in der Bundesrepublik Deutschland: Zur räumlichen Organisation der Tagespresse und ihren Zusammenhängen mit dem Siedlungsystem - Blotevogel, Hans Heinrich (ERDKUNDE, 1984)
Although recent human and regional geographical research has hardly dealt with the spatial organization of daily newspapers, this topic seems to be of growing interest to geographers. Because functional regions of central places are as well communication regions as regional advertisement markets, they determine the system of publication places and circulation areas of daily news papers. On the other hand the mass medium newspaper stabilizes the existing central place orientations and ties in with living spaces through spatially selective information flows. The existence of regional newspaper markets and their dependence on the settlement system is empirically examined according to the three most important types of newspapers: (i) Mass newspapers (penny press, boulevardnewspapers), (ii) subscription newspapers with national circulation, (iii) subscription newspapers with regional or local circulation. The spatial organization of the sub-market of mass newspapers is characterized by a close dependence upon the system of the highest ranking places. Even the Bild-Zeitung, the sole German boulevard newspaper (roughly tabloid) with national circulation and by far the largest German newspaper (circulation 6.4 mill.), was adjusted to the spatial market segmentation through a complex system of regional and local editions. Also the few subscription newspapers with national circulation are exclusively published in the highest ranking centres. Never theless they distribute large parts of their circulation in the respective regions. As the result of the lack of a national metropolis the places of publication are distributed among the regional metropolitan cities of Frankfurt, Hamburg, and Munich. On the other hand, the preconditions for a newspaper with a national circulation are lacking in the large industrial agglomeration of Northrhine Westphalia due to its polycentric structure. The locations and circulation areas of regional subscription news papers show particularly close connections with the system of central places and their market areas. The most newspapers are published in higher ranking central places, their political covers are produced by complete editorial boards and they are distributed over the entire hinterland of the place of publication. Local editions of these newspapers are published in several lower ranking centres of the respective hinterlands. Such a hierarchical organization yields an optimal adaption to the spatial market conditions. In reality interfering influences nevertheless cause manifold departures from this model, as the empirical results for the whole Federal Republic and for the regional example of eastern Westphalia show. In this region, for example, both the leading subscription newspapers are published in the sole higher ranking regional centre (Bielefeld) and are circulated through several local editions over the whole region, so that a general verification of the model can be remarked, but there are moreover two independent local news papers with their own editorial boards in smaller towns (Minden and Oelde). Finally, some further open questions are pointed out and a plea is made for an intensified examination of the daily press from a human and regional geographical point of view.